Evaluation of a particle trap laser desorption mass spectrometer (PT-LDMS) for the quantification of sulfate aerosols. Issue 2 (1st February 2016) - Ozawa, Y.; Takeda, N.; Miyakawa, T.; Takei, M.; Hirayama, N.; Takegawa, N.
Abstract: A particle trap laser desorption mass spectrometer (PT-LDMS) has been developed for the online measurements of the chemical composition of submicron aerosol particles. The PT-LDMS was evaluated by both laboratory and ambient measurements, with the focus being the quantification of sulfate aerosols. Ammonium sulfate ((NH4 )2 SO4 ) is generally the predominant form of sulfate aerosols in urban air; hence, it is used as a material for laboratory experiments and calibration. Major fragments of (NH4 )2 SO4 were observed at mass-to-charge ratios ( m / z ) of 48 (SO + ) and 64 (SO2 + ). The dependence of sensitivity (expressed as the ratio of m / z 48 signal to sulfate mass) on laser power and cell temperature was investigated. An intercomparison of PT-LDMS with a commercial sulfate particle analyzer (SPA) and filter sampling was performed in Tokyo. Good agreement was observed between SPA and filter analysis (slope = 0.98, r 2 = 0.99). Although the mass concentration of sulfate measured by PT-LDMS exhibited a tight correlation with that measured by SPA, the mass concentration measured by PT-LDMS tended to underestimate that measured by SPA (slope = 0.70, r 2 = 0.96). While the discrepancy can be mainly attributed to the difference in size cut between PT-LDMS (approximately PM1 ) and SPA (PM2.5 ), differences in vaporization efficiency were also found to be important. Copyright © 2016 American Association for Aerosol Research